Functional responses to multiple sequential abiotic stress (waterlogging-drought) in three woody taxa with different root systems and stress tolerance - Quiñones Martorello, Adriana; Gyenge, Javier; Colabelli, Mabel Noemí; Petigrosso, Lucas R; Fernandez, María Elena (Wiley, 2024)
There is generally a trade-off in the resistance to drought and to waterlogging. However, several species are sequentially subjected to both stressors in many environments. We evaluated the ecophysiological strategies to cope with multiple sequential stress of waterlogging and drought (W + D) of three taxa differing in stress resistance and root morphology: the phreatophic Eucalyptus camaldulensis (Ec) and two shallow-rooted willow clones: Salix matsudana x Salix alba (SmxSa) and Salix nigra (Sn4). Individuals of the three taxa were grown in pots and assigned to either of four treatments: Control (well-watered plants), well-watered followed by drought (C + D); waterlogged for 15 days followed by drought (W15d + D) and waterlogged for 30 days followed by drought (W30d + D). Biomass allocation, growth (diameter, height, length of leaves, and roots), specific leaf area, stomatal conductance, water potential, hydraulic conductivity of roots and branches, leaf C13and root cortical aerenchyma formation were determined at different stages of the experiment. Ec growth was not affected by W + D, developing tolerance strategies at leaf and whole plant levels. Differential effects of W + D were observed in both Salix clones depending on the time of waterlogging. In Sn4 and SmxSa, the root biomass was affected in W15d + D treatment, but a root tolerance response (aerenchyma and adventitious root formation) was observed in W30d + D. In the three taxa, and contrary to expectations, the previous exposure to a waterlogging period did not increase the susceptibility of the plants to a subsequent drought event. On the contrary, we found tolerance, which depended on the time of waterlogging exposure.